Avian Influenza Antibody Titer Of Laying Hens in Production Phase At District Penebel Tabanan Regency - Haris Muhamad Ikhsan (Journal of Applied Veterinary Science And Technology, 2021)
Background: The virus of Avian Influenza (AI) H5N1 has become endemic in Indonesia since 2003. In 2012, the Avian Influenza outbreak at District Penebel caused chickens mortality in large numbers. One of the efforts to prevention the Avian Influenza outbreak is by vaccination. Therefore, supporting AI vaccination program needs diagnostic methods from post-vaccinated chickens that produce antibody titer by Hemagglutination Inhibition (HI) test. Purpose:  The study aims to monitor the antibody of Avian Influenza phase I and phase II production in laying hens at District Penebel, Tabanan Regency. Method: 131 serum samples were collected from hens serums at poultry which has been sampled before. The serum sample is tested by Hemagglutination Inhibition (HI) test to calculate antibody titer. The serum is protective if the titer reacheas 24 or more, and the serum is unprotective if the titer is under 24. Data presented in 2x2 cross-sectional study contingent tabel and analyzed by Chi-Square (X2) non-parametric with the distribution. Results: Protective percentage of immunity level in production phase I in laying hens at District Penebel is 60,3%, whereas on production phase II is 43,6%. Data from the 2x2 contingent table showed an odd ratio of 1,9. The result of the Chi-Square (X2) analysis statistic represents immunity levels between production phase I and II are non-significance (p>0,05). Conclusion: Production phase I in laying hens has an immunity level 1,9x higher than production phase II. There is an association between the production phase and the protective immunity level of Avian Influenza.